LGR4, Not LGR5, Enhances hPSC Hematopoiesis by Facilitating Mesoderm Induction via TGF-Beta Signaling Activation - Yu Wang; Hongtao Wang; Jiaojiao Guo; Jie Gao; Mengge Wang; Meijuan Xia; Yuqi Wen; Pei Su; Ming Yang; Mingyao Liu; Lihong Shi; Tao Cheng; et al. (Cell Reports, 2020)
Summary: Attempts to generate functional blood cells from human pluripotent stem cells (hPSCs) remain largely unsuccessful, mainly due to the lack of understanding of the regulatory network of human hematopoiesis. In this study, we identified leucine-rich-repeat-containing G-protein-coupled receptor 4 (LGR4) as an essential regulator of early hematopoietic differentiation of hPSCs. The deletion of LGR4 severely impairs mesoderm development, thereby limiting hematopoietic differentiation both in vitro and in vivo. In contrast, LGR5 is dispensable for hPSC hematopoiesis. The four R-spondin proteins show differential activities and dependencies on LGR4 in hematopoietic differentiation. The deletion of LGR4 almost entirely abolishes the enhancement induced by R-spondin1 and R-spondin3, but not R-spondin2. In addition, ZNRF3 is required for the response of R-spondin1–R-spondin3. At the mechanistic level, LGR4 regulates transforming growth factor beta (TGF-beta) signaling to control hematopoietic differentiation. Together, our results reveal vital roles of LGR4 in hematopoietic development and uncover distinct functions and underlying mechanisms for R-spondins.